High pressure inertial focusing for separating and concentrating bacteria at high throughput. (27th June 2017) - Cruz, J; Hooshmand Zadeh, S; Graells, T; Andersson, M; Malmström, J; Wu, Z G; Hjort, K
Abstract: Inertial focusing is a promising microfluidic technology for concentration and separation of particles by size. However, there is a strong correlation of increased pressure with decreased particle size. Theory and experimental results for larger particles were used to scale down the phenomenon and find the conditions that focus 1 µ m particles. High pressure experiments in robust glass chips were used to demonstrate the alignment. We show how the technique works for 1 µ m spherical polystyrene particles and for Escherichia coli, not being harmful for the bacteria at 50 µ l min −1 . The potential to focus bacteria, simplicity of use and high throughput make this technology interesting for healthcare applications, where concentration and purification of a sample may be required as an initial step.